Digitalization and Cross-Border Tax Fraud: Evidence from E-Invoicing in Italy - Marwin Heinemann; Wojciech Stiller (Center for Economic Studies and ifo Institute (CESifo), 2023)
The digitalization of transaction processes through tools such as electronic invoicing (e-invoicing) aims to improve tax compliance and reduce administrative costs. Another important aspect of digitalization is its potential to reduce tax evasion. We analyze the impact of the widely introduced e-invoicing in Italy on cross-border value-added tax fraud. As a proxy for this tax fraud, we make use of the discrepancy in trade data that is double-reported in both the importing and exporting country (trade gap). We calculate trade gaps based on product flows on the most detailed level between Italy and the remaining countries of the European Union. Our results suggest a significant decline in cross-border fraud in response to the introduction of mandatory e-invoicing, providing an important rationale for the application of this measure by other countries. Furthermore, we estimate that e-invoicing decreased the Italian revenue loss by exteuro0.6 billion to exteuro1 billion in 2019. This is in line with the statements of the Italian Ministry of Finance, which are probably based mainly on the revenue development. In this context, we underpin the suitability of the trade gap as an approach for the study of anti-fraud measures and provide a more accurate estimate of cross-border fraud. In addition, our study suggests that fraudsters shift their activities to similar products and drive honest traders out of the market.
Keywords: F14; H21; H26; K34; K40; 330; e-invoicing; digitalization; international trade; VAT fraud; trade gap